Exploring The Effects of Cultural, Attitudinal, Language and Emotional Barriers on Job Performance at ABC Company - Omar, Siti Sarah; Ngui, Laurence Yew Jin (Journal of Techno-Social, 2024)
There are four sorts of communication barriers that are Attitudinal Barriers, Cultural Barriers, Language Barriers, and Emotional Barriers. People with opposing attitudes, ideals, and discrimination are major causes of workplace communication breakdown. Embracing differences allows us to draw on a greater spectrum of thoughts, ideas, experience, and expertise. The scope of this study is to explore the effects of cultural barriers, attitude barrier, language barriers and emotional barriers on job performance of workers in the organization. The method used in this study was a qualitative methodology using in-depth interview method with 8 respondents who are among managers, executives, and clerks. This study found out that, llanguage barriers arise when persons do not speak the same language and dialect or do not have equal proficiency in a language, while emotional barriers are those who are frustrated with financial issue, increment, promotion, and compliment from employer. Besides that, attitude barrier happens when someone is overly self-centered and believes that their ideas, thoughts, and viewpoints are more valuable than those of others. Finally, culture barriers are people who live in a different way of lifestyle, clothes, mentality, beliefs and the way they interact with each other. This study provide implications and recommendations for future study.